2015
DOI: 10.1002/chem.201501324
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations of the Stereoselective Synthesis of P‐Stereogenic Phosphine Oxides

Abstract: An efficient enantioselective strategy for the synthesis of variously substituted phosphine oxides has been developed, incorporating the use of (1S,2S)-2-aminocyclohexanol as the chiral auxiliary. The method relies on three key steps: 1) Highly diastereoselective formation of P(V) oxazaphospholidine, rationalized by a theoretical study; 2) highly diastereoselective ring-opening of the oxazaphospholidine oxide with organometallic reagents that takes place with inversion of configuration at the P atom; 3) enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…and analyzed by X-Ray diffraction. It appeared that the inversion of configuration at the phosphorus atom, already observed during our previous study, 16 was also confirmed in the ring opening of oxazaphospholidine R P -3. 27 In addition, the The same methodology was applied to the β-anomer (Table 1, entry 3) but the desired phosphinate 7 was formed with a low selectivity (d.e.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…and analyzed by X-Ray diffraction. It appeared that the inversion of configuration at the phosphorus atom, already observed during our previous study, 16 was also confirmed in the ring opening of oxazaphospholidine R P -3. 27 In addition, the The same methodology was applied to the β-anomer (Table 1, entry 3) but the desired phosphinate 7 was formed with a low selectivity (d.e.…”
Section: Resultssupporting
confidence: 82%
“…We were pleased to observe that the previously optimized conditions 16 proved once again successful on glucopyranoside derivatives S P -5 and R P -6. Indeed, 6.0 equiv.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations